A Novel Autosomal Recessive Candidate Gene Responsible for RASopathy-Like Phenotype and Bone Marrow Failure: RASA3 - Ayaz, Akif; Doğru, Zeynep; Kök, Kıvanç; Bayram, Nihan; Yaman, Yöntem; Köseoğlu, Abdullah Hüseyin; Yiğitbaşı, Türkan; Öztürk Demir, Aslı Güner; Yüksel, Elçin; Dundar, Burcu; Çaralan, Erdal Fırat; Nepesov, Serdar; Elli, Murat (Journal of Pediatric Genetics, 2023)
Although many genetic etiologies, such as Fanconi anemia, Shwachman–Diamond syndrome, dyskeratosis congenita, and Diamond–Blackfan anemia, from hereditary bone marrow failure are known today, the responsible gene remains unknown in a significant part of these patients. A 6-year-old girl, whose parents were first-cousin consanguineous, was referred to the pediatric hematology department due to growth retardation, thrombocytopenia, neutropenia, and anemia. The patient had low-set ears, pectus excavatum inferiorly, and cafe-au-lait spots. In whole-exome analysis, p.K385T (c.1154A > C) variant in the RASA3 gene was detected as homozygous. The amino acid position of the alteration is located in the conserved and ordered region, corresponding to the Ras GTPase activation domain (Ras-GAP) in the center of the protein. Importantly, most of in silico prediction tools of pathogenicity predicts the variant as damaging. RASopathies, which are characterized by many common clinical findings, such as atypical facial features, growth delays, and heart defects, are a group of rare genetic diseases caused by mutations in the genes involved in the Ras-MAPK pathway. The findings in this patient were consistent with the RASopathy-like phenotype and bone marrow failure. Interestingly, enrichment of RASopathy genes was observed in the RASA3 protein–protein interaction network. Furthermore, the subsequent topological clustering revealed a putative function module, which further implicates RASA3 in this disease as a novel potential causative gene. In this context, the detected RASA3 mutation could be manifesting itself clinically as the observed phenotype by disrupting the functional cooperation between the RASA3 protein and its interaction partners. Relatedly, current literature also supports the obtained findings. Overall, this study provides new insights into RASopathy and put forward the RASA3 gene as a novel candidate gene for this disease group.
Keywords: RASA3; RASopathy; bone marrow failure; p.K385T; c.1154A > C